Adsorption of Phenol and p-Nitrophenol on Activated Carbon: Determination of Effective Diffusion Coefficients - Enrique Costa; Guillermo Calleja; Luis Marijuan (Adsorption Science & Technology, 1987)
Adsorption of phenol and p-nitrophenol in aqueous solution on granular activated carbon has been studied in a stirred-tank system. Equilibrium isotherms and concentration decay curves were obtained experimentally for each adsorbate in the finite batch adsorber, for three temperatures in the range 274-313 K. Effective internal diffusion coefficients, Di, of the two adsorbates were calculated by means of a mathematical model of diffusion-adsorption that takes into account ordinary liquid phase diffusion and surface diffusion mechanisms. Surface diffusion coefficients, DS, were also calculated and correlated with temperature and surface coverage. Isosteric heat of adsorption and activation energy for the adsorption of p-nitrophenol were calculated; values obtained are between those of characteristic physical and chemical adsorption.